A survey on psychological effects following administration of the first dose of COVID-19 (Oxford-AstraZeneca-Covishield) vaccine in Sri Lanka: experience among the medical community - Rowel, Warnakula Weerasooriya Jayathilaka Sashka Madushi; Asanka Kodithuwakku, Kodithuwakku Arachchilage Sajith Uditha; Sanjeewa, Jayawardhana Mudiyanselage Pradeepa (International Journal Of Community Medicine And Public Health, 2021)
Background: Research on psychoimmunology has demonstrated a bidirectional relationship between the immune system and the brain. Although the evidence is conflicting, few studies are suggesting a temporal association between neuropsychiatric disorders and some vaccines. However, research is scarce in this area. We observed that some recipients experienced various transient psychological symptoms in addition to physical symptoms following administration of the first dose of Oxford-AstraZeneca-Covishield vaccine in Sri Lanka. The objective of this survey was to assess the nature, associations and duration of the psychological symptoms observed following the vaccine. Methods: A cross-sectional online survey was conducted among the medical community in the age range of 25-63 years, who received the first dose of the vaccine. The questionnaire inquired demographic details, physical symptoms, psychological symptoms, duration of symptoms and their view on taking the second dose and recommending it to family or friends. Results: The majority (94.6%) of the participants had experienced some form of a physical symptom and 85.2% experienced at least one psychological symptom. Those who had fever experienced a higher rate of psychological symptoms compared to those who hadn’t. However, this difference was not significant. The majority developed symptoms after 12 hours of receiving the vaccine and the symptoms lasted for less than 48 hours. Conclusions: Notable rates of psychological symptoms were observed in recipients of the first dose of Oxford-AstraZeneca-Covishield vaccine. However, these symptoms were self-limiting. Further studies are needed to ascertain if these observations are significant.